1982
DOI: 10.1002/ijc.2910290204
|View full text |Cite
|
Sign up to set email alerts
|

Serological mass survey for early detection of nasopharyngeal carcinoma in wuzhou city, china

Abstract: A serological mass survey was carried out in Wuzhou City of the Guangxi Autonomous Region, China. Sera were collected from 12,932 persons between the ages of 40 and 59. The positive rate of VCA/IgA antibody-positive person was 5.3%, but no EA/IgA antibody was found in sera from VCA/Iga-negative persons. Thirteen and nine nasopharyngeal carcinoma (NPC) patients were detected from the VCA/Iga and EA/IgA antibody-positive persons, respectively. With the present combination method the detection rate of NPC for 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
163
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 2 publications
1
163
0
2
Order By: Relevance
“…Previous population studies carried out in high-incidence areas for NPC estimated the occurrence of the cancer among apparently healthy subjects having an elevated serum level of VCA IgA to be about 1% per year. 4,5,7 In practice, this serves to alert the individuals and clinicians to early symptoms of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population studies carried out in high-incidence areas for NPC estimated the occurrence of the cancer among apparently healthy subjects having an elevated serum level of VCA IgA to be about 1% per year. 4,5,7 In practice, this serves to alert the individuals and clinicians to early symptoms of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…58 In fact, a panel of serological tests is used fairly successfully to screen for nasopharyngeal carcinoma in high risk populations, to assign prognosis in those patients who are affected, and to detect early relapse after therapy. 59 Analogous studies are underway in gastric carcinoma patients who likewise harbor high serological titers against EBV.…”
Section: Ebv Serologymentioning
confidence: 99%
“…1 Although several previous studies [2][3][4][5] have reported on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains to be defined. Circulating cell-free EBV DNA is detectable in the plasma of 96% of NPC patients 6 by quantitative real-time polymerase chain reaction (PCR) and has been shown to be a useful marker in prognostication 7 as well as residual disease detection.…”
Section: Dear Sirmentioning
confidence: 99%